POSSIBILE EMERGENZA DA RHABDOVIRUS (EVEX) SULLE POPOLAZIONI SELVATICHE DI ANGUILLA ANGUILLA: PRIMO MONITORAGGIO POTENTIAL EMERCENCY BY RHABDOVIRUS (EVEX) ON WILD POPULATION OF ANGUILLA ANGUILLA: FIRST MONITORING - Pastorino Paolo; Caruso Claudio; Gustinelli Andrea; Culurgioni Jacopo; Righetti Marzia; Masoero Loretta; Fioravanti Marialetizia; Pizzul Elisabetta; Prearo Marino (Associazione Italiana Ittiologi Acqua Dolci (A.I.I.A.D.), 2018)
The European eel (Anguilla anguilla) is a catadromous species evaluated as Critically Endangered (CR) by IUCN based on the significant population decline occurred in the last 30 years. The threats on this species are numerous, among these, the presence of the nematode Anguillicoloides crassus and the infection caused by rhabdovirus EVEX (Eel virus European X) represent the major causes of reduction efficiency in eel’s swimming performances, compromising the migration capacity of the species. For the purpose to carry out an experimental test regarding the artificial spawning of 56 this species, some specimens of A. anguilla were captured from some watercourses in Sardegna Region. A few days later, some morbidity event occurred with the appearance of clinical signs as lethargy and hemorrhagic skin lesions of lateral line, fins and head. For this reason, between 2016 and 2017, 53 individuals of A. anguilla were sampled from different watercourses of Sardegna Region. In particular, 20 from Rio Pramaera (Municipality of Lotzorai, OG), 13 from Rio Barca (Municipality of Alghero, SS) and 20 from Flumedosa River (Municipality of Villaputzu, CA) in order to verify the possible presence of the virus in wild populations. The virological analysis (cell lines and PCR end point) were negative for all samples. Nevertheless, it is important to carried out a health monitoring on wild population to investigate the etiological role and the distribution of the virus in wild population of eels.